Development of self-critical abilities and values in students using digital games-based learning - Zuo, Chunning (Frontiers in Psychology, 2023)
Young people are the driving force of society. Therefore, the well-being of society itself depends on what values and ideals they carry into adulthood. The purpose of this study was to identify and describe the values of contemporary Chinese youth in the context of their future life goals and to analyze how self-criticism shapes students’ depressive tendencies with the use of digital games. This study was conducted at Shaanxi Technical College of Finance and Economics with 157 Chinese students between the ages of 18 and 25. One hundred nine girls and forty-eight boys were randomly selected for the study. The study was conducted in a Chinese cultural context using the method of experiment with a survey, statistical, and correlational data analysis. Correlation analysis showed that the correlation between self-criticism and N/NE is strong (rs ¼ 0.50–0.65), but it was most related to the positive emotional component of E/PE. Thus, no obvious and serious reasons for the development of depression in young people were found. The results showed that digital games cannot influence the development of self-critical abilities of students, however, they can be a high-quality tool in psychological work with students to determine depressive moods, an overestimated level of self-criticism, and other problems that prevent them from learning. This article has implications for further research in education, as it may provide a basis for developing and improving new methods of constructing curricula. They can be aimed at defining special attention to the psychological state of students to prevent depressive states caused by high levels of self-criticism.